Assessment of radiation protection knowledge and practices among radiographers in the central region of Ghana - Emmanuel Fiagbedzi; Philip Nii Gorleku; Savanna Nyarko; Adomako Asare; Gideon Ackah Ndede (Radiation Medicine and Protection, 2022)
Objective: To assess the radiation protection practices and knowledge among radiographers in the central region of Ghana. Methods: A cross-sectional study was carried out among practicing radiographers in three selected hospitals. The study was carried out from January to October 2021. A self-administered questionnaire comprising three sections was given out to 20 participants to answer. Data were analyzed statistically using the Statistical Package for Social Sciences (SPSS) version 25.0 and logistic regression analysis. Results: The study revealed that over ninety percent of the radiographers had dosimeters but only 25% wear them always. Adherence to radiation protection measures and practices was found to be generally fairly satisfactory, but was high in the age group 35–45. However, Knowledge of radiation protection practices amongst the radiographers was generally high. Working experience of fewer than 5 years (P ​= ​0.035) gave a high odds ratio (OR) and was of a significant value in determining the radiation training and courses undertaken by these radiographers. Conclusions: The adherence to radiation protection practices was fairly satisfactory, and the knowledge of radiation protection practices was generally high, but that is not enough. There is more room for improvement to ensure knowledge is put into practice to enhance proper safety measures, ensure effective work, and overall reduce the negative effects of ionizing radiation.